2019
DOI: 10.1038/s41409-019-0766-z
|View full text |Cite|
|
Sign up to set email alerts
|

PDGFB-expressing mesenchymal stem cells improve human hematopoietic stem cell engraftment in immunodeficient mice

Abstract: The bone marrow (BM) niche regulates multiple hematopoietic stem cell (HSC) processes. Clinical treatment for hematological malignancies by HSC transplantation often requires preconditioning via total body irradiation, which severely and irreversibly impairs the BM niche and HSC regeneration. Novel strategies are needed to enhance HSC regeneration in irradiated BM. We compared the effects of EGF, FGF2, and PDGFB on HSC regeneration using human mesenchymal stem cells (MSCs) that were transduced with these facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 44 publications
0
48
0
Order By: Relevance
“…Overall, co-transplantation of the BM-derived MSCs into humanized mice can improve human HSPC maintenance and expansion, and improve reconstitution of the human hemato-lymphoid system in humanized mice. Furthermore, recent studies have used genetically engineered MSCs to deliver additional human factors to support human hematopoiesis, or to facilitate the expansion and maintenance of HSPCs to allow serial transplantation and generation of larger quantities of humanized mice ( 118 , 119 ).…”
Section: Principle #3: Supporting the Development Of Engrafted Human mentioning
confidence: 99%
“…Overall, co-transplantation of the BM-derived MSCs into humanized mice can improve human HSPC maintenance and expansion, and improve reconstitution of the human hemato-lymphoid system in humanized mice. Furthermore, recent studies have used genetically engineered MSCs to deliver additional human factors to support human hematopoiesis, or to facilitate the expansion and maintenance of HSPCs to allow serial transplantation and generation of larger quantities of humanized mice ( 118 , 119 ).…”
Section: Principle #3: Supporting the Development Of Engrafted Human mentioning
confidence: 99%
“…Secreted PDGF-BB is involved in cancer progression via multiple mechanisms. PDGF-BB induces the stem cell phenotype either by accelerating the maturation of collagen chains through increased LOX activity 35 or by inducing both perivascular and satellite cell gene expression to acquire improved migration of human hematopoietic cells 36,37 . Our data showed that PDGFB silencing abrogated the RASSF1A depletion-induced malignant phenotypes of NPC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Various modi cations of MSCs have been attempted to improve their survival rates and therapeutic e cacy [31,32,34,35]. Attempts to improve stem cell survival, metabolism, or migration ability have focused on genetic modi cations to knock-out or knock-in speci c genes [36][37][38]. However, the clinical application of genetically-modi ed MSCs is associated with the risk of unexpected genetic mutations resulting in tumor formation [39].…”
Section: Discussionmentioning
confidence: 99%